Effectiveness of Project-Based Learning Model Teaching Tools on Fantasy Bun Material - A., Annisa Anugrah; Wahyuningsih, Sri Endah; Qudus, Nur (Universitas Negeri Semarang, 2023)
Learning activities on fantasy hair bun material require students to create the design of the arrangement before engaging in practical activities. However, the practical results of the fantasy hair bun do not align with the students' initial designs. Students find it challenging to produce fantasy hair bun arrangements that match their created designs. This study aims to analyze the feasibility, practicality, and effectiveness of the Project-Based Learning teaching materials on fantasy hair bun. The research adopts the Research and Development (RD) method with the ADDIE procedure, which consists of Analyse, Design, Development, Implementation, and Evaluation stages. The research design used a Quasi-Experiment. The results of the feasibility test, based on assessments by three experts, produced an average score of 3.64, indicating a highly feasible category. The practicality test results, conducted with 36 students, produced a total score of 1909 with an average score of 53.2, falling under the highly practical category. The effectiveness test used the N-gain test which was carried out in both classes, namely the experimental class and the control class. The results of the N-gain calculation of the experimental class were 0.42 while the average N-gain of the control class was 0.10, so learning using the PjBL model teaching materials was more effective in improving student learning outcomes on bun material development research resulted in a product in the form of Project-Based Learning model teaching materials that have a positive and beneficial impact on fantasy hair bun learning activities. Based on the research findings, the developed Project-Based Learning teaching materials are highly feasible, highly practical, and effective for use in fantasy hair bun material learning.